Schizophrenia Patients With Prevotella-Enterotype Have a Higher Risk of Obesity - Liang, Ying; Shen, Yang; Li, Gaofei; Yuan, Ye; Zhang, Meng; Gao, Jiayu (Frontiers in Psychiatry, 2022)
Recent studies have indicated the critical influence of gut microbiota on the occurrence of obesity. There is a significant risk of obesity in people with schizophrenia. This work proposed that the disorder of gut microbiota in patients with schizophrenia was based on microbial enterotypes. 97 schizophrenia patients and 69 matched health controls were eligible. The fresh feces of all subjects were collected to complete 16S rRNA sequence. Statistical analysis was performed to identify the intestinal type of gut microbiota and analyze their potential effects on metabolic function. Patients with enterotype-P had a higher BMI than that of the others. Several differences in the gut microbes of enterotypes-prevotella were found between patients and controls. Proteobacteria and Firmicutes had significantly higher abundance in patients’ group with enterotypes-prevotella. The Bacteroidetes had higher abundance in health controls with enterotypes-prevotella. Different metabolic pathways of the microbiota with the enterotype-prevotella were identified in the subjects categorized in different BMI intervals. The schizophrenia patients had a significantly higher BMI than that of health controls. Patients with enterotype-prevotella had a higher BMI. Therefore, the enterotype- prevotella might have a critical influence on a variety of metabolic pathways to disrupt the metabolism of glucose and lipid in human body.